2009
DOI: 10.1103/physrevb.80.155318
|View full text |Cite
|
Sign up to set email alerts
|

Excitonic behavior in self-assembled InAs/GaAs quantum rings in high magnetic fields

Abstract: We investigate the exciton energy level structure of a large ensemble of InAs/GaAs quantum rings by photoluminescence spectroscopy in magnetic fields up to 30 T for different excitation densities. The confine m ent o f an electron and a hole in these type I quantum rings along with the Coulomb interaction suppress the excitonic Aharonov-Bohm effect. We show that the exciton energy levels are nonequidistant and split up in only two levels in m agnetic field, reflecting the ringlike geometry. A model, based on r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 31 publications
0
18
0
1
Order By: Relevance
“…12-17) have stimulated theoretical and experimental studies of the AB oscillations in the persistent currents carried by single-and few-particle states (see, e.g., Refs. [18][19][20][21][22][23][24]. Using an ultrasensitive torsion magnetometer, AB oscillations in the magnetic moment of In x Ga 1−x As self-assembled quantum rings have been observed 18 with a magnitude of oscillation as large as 60% to 70% of the corresponding magnitude in an ideal ring.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…12-17) have stimulated theoretical and experimental studies of the AB oscillations in the persistent currents carried by single-and few-particle states (see, e.g., Refs. [18][19][20][21][22][23][24]. Using an ultrasensitive torsion magnetometer, AB oscillations in the magnetic moment of In x Ga 1−x As self-assembled quantum rings have been observed 18 with a magnitude of oscillation as large as 60% to 70% of the corresponding magnitude in an ideal ring.…”
Section: Introductionmentioning
confidence: 98%
“…The AB oscillations have also been experimentally detected in the excitonic magnetophotoluminescence spectra of single quantum rings, 23 although the corresponding effect is rather weak and it can become unobservable in the spectra averaged over an ensemble of nonidentical rings. 22 Also, the successful experimental detection of the AB effect in the magnetic moment of single-electron nanorings 18 has appeared to be a rather challenging task because the magnetization signal is extremely weak even for a large assembly of rings. It has been shown that imperfections in the ring geometry such as local potential fluctuations can severely affect the magnitude of the anticipated AB effect in the optical, electronic, and magnetic signals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Todo esto apuntando al objetivo central que es encontrar las autofunciones y autoenergías del Hamiltoniano del sistema. Tales cálculos han sido desarrollados para investigar distintas clases de problemas, como son: (1) espectros de electrones y huecos en anillos cuánticos aislados (Filikhin, et al, 2006) y dobles (Culchac, et al, 2008); (2) estados de impurezas aceptoras y donadoras poco profundas en anillos cuánticos con confinamiento rectangular bajo los efectos cruzados de campos eléctrico y magnético (Bruno-Alfonso & Latgé, 2000); (3) estados de impurezas poco profundas en puntos cuánticos parabólicos y semiparabólicos (Assaid, et al, 2008), y (4) complejos excitónicos en puntos cuánticos verticalmente acoplados bajo los efectos de campo magnético (Kleemans, et al, 2009). Los resultados más importantes pueden ser resumidos así: (1) los niveles excitónicos no aparecen equidistantes y se desdoblan con el campo magnético, reflejando con ello las características asociadas a la geometría de los anillos, (2) las oscilaciones de Aharonov-Bohm de excitones, que son características de anillos unidimensionales no aparecen en sistemas de dimensiones finitas, y (3) los campos eléctricos generan nuevas reglas de selección para las transiciones inter e intrabanda.…”
Section: Introductionunclassified
“…One more related study reports observation of OAB oscillations in the energy and the intensity of the PL of a multi-layer type-II Si/Ge QD structure [11]. In the experiments of the above references the type-II band alignment provides favorable conditions for the observation of the OAB-effect, whereas a type-I quantum ring is predicted to have a relatively weak OAB owing to the Coulomb attraction in the exciton [12].…”
mentioning
confidence: 99%